COVID-19 Vaccine Hesitancy in ASEAN: Insights from a Multi-wave Survey Database from July 2020 to March 2021 - Hartigan-Go, Kenneth Y (Archīum Ateneo, 2021)
Objectives. Early studies on COVID-19 vaccine hesitancy showed varied intensity across countries, which was linked to various factors such as socio-economic conditions, information sources, and issues of trust in government, scientific experts, and the health sector. This study aims to evaluate the determinants of vaccine hesitancy to offer insights into the strategies that may be successful in designing communications campaigns for enhanced vaccination uptake. Methods. Through logistic regression, this study examines correlates of survey data from five Southeast Asian countries, namely Indonesia (ID), Malaysia (MY), Philippines (PH), Thailand (TH), Vietnam (VN) collected by the Massachusetts Institute of Technology Initiative on Digital Economy and Facebook between July 2020 and March 2021. Results. Some significant determinants at the 5% or 1% level of significance of COVID-19 vaccine hesitancy in the countries of interest include gender [ID: 1.17 (1.01, 1.15), MY: 1.35 (1.2,1.53), PH: 1.92 (1.68,2.19), VN: 1.28 (1.04,1.58)], age [MY:1.11 (1.06,1.17), PH: 0.92 (0.88, 0.97), TH: 1.17 (1.11, 1.23)], knowing someone who tested positive for COVID-19 [ID: 0.75 (0.65,0.88), MY: 0.82 (0.71,0.95), PH: 0.76 (0.67, 0.87), TH: 0.76 (0.59, 0.99), VN: 0.72 (0.54,0.97)], and perceived effectiveness of mask wearing [ID: 0.83 (0.74, 0.94), MY: 0.86 (0.79, 0.95), TH: 0.88 (0.8,0.98)]. Vaccine hesitancy is particularly strong among women in 3 countries—peaking at 52% in Indonesia, 42% in Malaysia, and 56% in the Philippines. Conclusion. Results from the survey highlight the significance of a targeted vaccine education and research campaign. This study calls for streamlining of communications campaigns towards messages that promote vaccine uptake in the region, while better targeting those groups most vulnerable guided by the empirical findings herein.